Efficacy of balloon angioplasty and stent placement in the treatment of central venous stenosis in patients with chronic kidney disease on hemodialysis - Valderrama-Treviño, Alan I.; Estrada, Fernando G. Ramírez; Sierra-Juárez, Miguel A.; Valenzuela, Marlon E. Lacayo (International Surgery Journal, 2024)
Background: Central venous stenosis is a common complication in hemodialysis patients, often caused by multiple long-term catheter use. This retrospective observational study evaluated the efficacy of balloon angioplasty and stent placement in treating central venous stenosis secondary to hemodialysis catheter use. Methods: A retrospective observational study was conducted at the Hospital General de México Dr. Eduardo Liceaga, analyzing clinical records of 16 chronic kidney disease patients diagnosed with central venous stenosis who underwent endovascular surgery between January 2022 and August 2024. The study evaluated demographic characteristics, comorbidities, stenosis location, and technical success. Statistical analysis included descriptive measures, Shapiro-Wilk test for normality, and paired Student's t-test (α=0.05) to compare pre- and post-angioplasty venous diameters. Results: The mean age of patients was 44.6±13.5 years, with a slight female predominance. The most common stenosis location was the right subclavian vein (31.2%), followed by the left brachiocephalic trunk (25%). Pre-procedure stenotic vessel diameter averaged 3.86±1.5 mm, increasing to 9.19±2.03 mm post-procedure. Statistical analysis showed a significant 138% increase in vessel diameter (p<0.001). Of the 16 procedures, 11 patients underwent successful angioplasty, with 37.5% requiring stent placement due to recoil greater than 30%. In 5 cases, crossing the occlusive lesion was not possible. Conclusions: The study demonstrated the effectiveness of balloon angioplasty and stent placement in treating central venous stenosis, with a statistically significant improvement in vascular diameter. However, further studies with long-term follow-up are needed to evaluate the durability of these results and optimize management of complex cases.